ANALYSIS OF POLYPEPTIDE PROFILES OF STRONGYLID NEMATODES USING SODIUM DODECYL SULPHATE POLYACRYLAMIDE GEL ELECTROPHORESIS - Arunkumar , S; Sharma , R L (Indian Journal of Veterinary Sciences and Biotechnology, 2010)
Polypeptide profile of soluble extract antigens (SEA) of referral nematodes viz., Haemonchus contortus, Bunostomum trigonocephalum and Oesophagostomum columbianum were analysed by sodium dodecyl sulphate polyacarylamide gel electrophoresis (SDS-PAGE). The SEA of H. contortus showed bands at 24.0, 29.0, 35.0, 43.0, 60.0, 94.0 and 106 kDa molecular weight whereas the SEA of B. trigonocephalum showed bands at 21.0, 29.0, 30.0, 47.0, 60.0, 94.0 and 101 kDa size. The SEA of O. columbianum revealed polypeptide bands at 29.0, 39.0, 54.0, 60.0, 94.0 and 112 kDa. It was also revealed that a common polypeptide bands at 29.0, 60.0 and 94.0 kDa were present in all three antigens.
Keywords: Antigenic profiles; gastro intestinal nematodes; SDS-PAGE